QSPR study on the bioconcentration factors of nonionic organic compounds in fish by characteristic root index and semiempirical molecular descriptors - ERDEM, SAFİYE (AMER CHEMICAL SOC, 2004)
The characteristic root index (CRI) was modeled together with four semiempirical molecular descriptors, namely-energies of the highest occupied and the lowest unoccupied molecular orbital (E-HOMO and E-LUMO), heat of formation (DeltaH(f)), and dipole moment (mu)-to predict the fish bioconcentration factor (BCF) of 122 nonionic organic compounds. The best fit equation found by forward multiple linear regression showed that the topology based CRI was the most important parameter. The addition of quantum chemical descriptors made only a slight improvement in the predictive capability of the Quantitative Structure-Property Relationship (QSPR) model. The CRI was followed by EHOMO. A two-parameter equation with a correlation coefficient of r = 0.921 was obtained for a diverse set of nonionic organic chemicals. Statistical robustness of the developed model was validated by modified jackknife tests where random deletion of a class of compounds and specific deletion of a set of compounds were both performed. The predictive accuracy of the proposed model was compared with the commonly used K-ow model and recently published studies in which BCF models were developed. Particular emphasis has been made to clearly define the boundaries for the application of the alternative developed model as well as the quality of estimates.
Keywords: WATER PARTITION-COEFFICIENTS; QUANTUM-CHEMICAL PARAMETERS; POLYCHLORINATED-BIPHENYLS; CONNECTIVITY INDEXES; COMPOUNDS PCOCS; PREDICTION; MODEL; BIOTRANSFORMATION; POLLUTANTS; QSAR